(untitled) (REMUNOM, 2026)
This article examines the legal repercussions of multiparental relationships in the Brazilian legal system, with emphasis on its effects on Inheritance Law and the jurisprudential construction of the Superior Court of Justice (STJ). The central problem is to assess the compatibility between the plurality of parental ties and the regime of legitimate succession outlined by the 2002 Civil Code. To this end, a qualitative approach is adopted, of a bibliographic and documentary nature, guided by the deductive method, to analyze the overcoming of the strictly biological paradigm in favor of a eudaimonistic conception of family relations, anchored in the principles of human dignity and affection. The study also considers the thesis established by the Supreme Federal Court in General Repercussion Theme 622, which recognizes the non-existence of hierarchy between the modalities of filiation, admitting the concomitance of parental ties with full legal effectiveness. In this context, the succession implications of multiparental relationships are investigated, especially regarding inheritance competition, the possibility of accumulating inheritance shares, and the expansion of kinship relations. It is concluded that multiparental relationships necessitate a functional reinterpretation of Inheritance Law.